TAK1 inhibition improves myoblast differentiation and alleviates fibrosis in a mouse model of Duchenne muscular dystrophy. Issue 1 (25th November 2020) - Xu, Dengqiu; Li, Sijia; Wang, Lu; Jiang, Jingwei; Zhao, Lei; Huang, Xiaofei; Sun, Zeren; Li, Chunjie; Sun, Lixin; Li, Xihua; Jiang, Zhenzhou; Zhang, Luyong
Abstract: Background: Transforming growth factor‐β‐activated kinase 1 (TAK1) plays a key role in regulating fibroblast and myoblast proliferation and differentiation. However, the TAK1 changes associated with Duchenne muscular dystrophy (DMD) are poorly understood, and it remains unclear how TAK1 regulation could be exploited to aid the treatment of this disease. Methods: Muscle biopsies were obtained from control donors or DMD patients for diagnosis ( n  = 6 per group, male, 2–3 years, respectively). Protein expression of phosphorylated TAK1 was measured by western blot and immunofluorescence analysis. In vivo overexpression of TAK1 was performed in skeletal muscle to assess whether TAK1 is sufficient to induce or aggravate atrophy and fibrosis. To explore whether TAK1 inhibition protects against muscle damage, mdx (loss of dystrophin) mice were treated with adeno‐associated virus (AAV)‐short hairpin TAK1 (shTAK1) or NG25 (a TAK1 inhibitor). Serum analysis, skeletal muscle performance and histology, muscle contractile function, and gene and protein expression were performed. Results: We found that TAK1 was activated in the dystrophic muscles of DMD patients ( n  = 6,  +72.2%, P  < 0.001), resulting in fibrosis ( +65.9% for fibronectin expression, P  < 0.001) and loss of muscle fibres (−32.5%, P  < 0.01). Moreover, TAK1 was activated by interleukin‐1β, tumour necrosis factor‐α, and transforming growth factor‐β1 ( P  < 0.01). Overexpression of TAK1 by AAV vectors further aggravated fibrosis ( n  = 8,  +39.6% for hydroxyproline content, P  < 0.01) and exacerbated muscle wasting (−31.6%, P  < 0.01) in mdx mice; however, these effects were reversed in mdx mice by treatment with AAV‐short hairpin TAK1 (shTAK1) or NG25 (a TAK1 inhibitor). The molecular mechanism underlying these effects may be related to the prevention of TAK1‐mediated transdifferentiation of myoblasts into fibroblasts, thereby reducing fibrosis and increasing myoblast differentiation. Conclusions: Our findings show that TAK1 activation exacerbated fibrosis and muscle degeneration and that TAK1 inhibition can improve whole‐body muscle quality and the function of dystrophic skeletal muscle. Thus, TAK1 inhibition may constitute a novel therapy for DMD.